Community-Based Tolerance Education Model for Urban Societies - Nenden, Nenden; Halim, Ilim Abdul; Shidqi, Abid Khofif Amri (Tashwirul Afkar, 2024)
This study aims to examine how the Sekolah Damai Indonesia (Sekodi) community implements experiential tolerance education within a pluralistic yet fragmented society in post-reformasi Indonesia. By using a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observations, and document analysis. The findings show that Sekodi’s model of community-based non-formal education successfully cultivates empathy, critical awareness, and social cohesion through dialogical and participatory learning spaces. This model challenges the limitations of top-down institutional approaches by positioning youth as co-creators of meaning and active agents of ideological transformation. The implications suggest that grassroots education can play a significant role in promoting peaceful coexistence and democratic resilience in culturally diverse societies. However, the study also reveals structural vulnerabilities due to the reliance on volunteers and informal infrastructure, which may threaten the sustainability and scalability of such initiatives. This research contributes original insights by framing tolerance education through the intersection of Weberian social action and Deweyan experiential learning, offering a practical model of peace education grounded in local contexts.